Non-steady state diagenesis of organic and inorganic sulfur in lake sediments. (1st December 2016) - Couture, Raoul-Marie; Fischer, Rachele; Van Cappellen, Philippe; Gobeil, Charles
Abstract: Sulfur controls the fate of many geochemical elements in lake sediments, including iron, phosphorus and environmentally important trace elements. We measured the speciation of pore-water and sediment-bound sulfur (aqueous sulfate and sulfides, elemental sulfur, iron monosulfide, pyrite, organic sulfur) and supporting geochemical variables (carbon, oxygen, iron) in the sediments of a perennially oxygenated and a seasonally anoxic basin of an oligotrophic lake in Québec, using a combination of pore-water analyses, sequential extractions and X-ray absorption near edge structure. A non-steady state early diagenetic model was developed and calibrated against this extensive dataset to help unravel the pathways and quantify the rates of S transformations. Results suggest that the main source of S to the sediments is the settling of organic ester-sulfate (R-O-SO3 -H). Hydrolysis of these compounds provides an additional source of sulfate for anaerobic microbial oxidation of sedimentary organic matter, releasing sulfide to the pore-water. Reduced solid-bound S species accumulate as thiols (R-SH) and iron sulfides in the perennially oxygenated and seasonally anoxic basin, respectively. The model-estimated rate constant for R-SH formation is lower than previously estimated for this particular lacustrine site, but similar to that proposed for marine shelf sediments. The solid sediment S profiles, however, carry the imprint of the time-dependent sulfate input to the lake. Iron sulfide enrichments formed during past decades of elevated atmospheric SO4 deposition are presently dissolving. In the sediments of the perennially oxygenated basin this reaction hampers the build-up of Fe(III) (oxy)hydroxide near the sediment–water interface.